Imagining the Feminist Imaginary Through Object-Based Research - Sanford, Kathy; Clover, Darlene (International Journal for Talent Development and Creativity, 2024)
Using objects-based research, feminist adult educators and museum curators shared and described artifacts of personal and professional meaning. These objects enabled participants in this feminist study to articulate ways in which we enact power and change, and ways in which we can imagine and create a more feminist world. Through this study we challenge systems of patriarchal colonial oppression, addressing inequities across gender as it connects with class, race and culture and showing how objects reveal alternative ways of seeing and shaping the world. In this paper we take up feminist object-based research as a way to step outside ‘patriarchal logic’ to reimagine the world through four themes: corporeal, including the body and objects worn on the body; communicative, which speak and narrative; protect, representing feminist action and power, and disappearing, referring to that which has been lost or made absent. These show recurring patterns and connections that collectively enable us to imagine a more equitable and just feminist world.